Integration host factor regulates antibiotic susceptibility through modulating alanine metabolism in Escherichia coli - Fu, Huan-zhe; Yuan, Si-chen; Jiang, Ming; Chen, Yu-Yan; Peng, Xuan-xian; Li, Hui (Frontiers in Microbiology, 2026)
PurposeThis study aimed to define how integration host factor (IHF) influences antibiotic susceptibility through metabolic regulation, using Escherichia coli ΔihfA and ΔihfB mutants.MethodsThe metabolic profiles of ΔihfA and ΔihfB mutants were analyzed by gas chromatography–mass spectrometry (GC–MS) versus the K12 parent. Antibiotic susceptibility was assessed by plate counting, proton motive force (PMF) by flow cytometry, and enzyme activities via 3-(4,5-Dimethylthiazol-2-yl)-2,5 -diphenyltetrazolium bromide (MTT) reduction.ResultsDeletion of ihfA and ihfB resulted in increased minimum inhibitory concentrations (MICs) and/or enhanced bacterial survival upon exposure to ampicillin, balofloxacin, or gentamicin. Both mutants exhibited global metabolic downregulation, with significantly reduced alanine levels identified as the most prominent biomarker. Consistent with these observations, enzymatic activities in the pyruvate cycle were impaired, and PMF was diminished. Exogenous alanine supplementation restored the pyruvate cycle and PMF level, thereby resensitizing the mutants to all three antibiotics. This effect was further corroborated by the use of the PMF inhibitor carbonyl cyanide m-chlorophenyl hydrazone, which abolished alanine-mediated antibiotic killing in ΔihfA and ΔihfB strains.ConclusionTogether, these results provide compelling evidence that IHF modulates antibiotic susceptibility through metabolic reprogramming, with alanine metabolism and PMF maintenance serving as key functional links.